Salt-corrosion-resistant modified concrete material and preparation method thereof
By adding basalt fibers and epoxy resin to the concrete, a dense protective layer is formed, which solves the problem of corrosion and freeze-thaw damage in harsh environments, and significantly improves its corrosion resistance and freeze-thaw resistance. , extends the service life of the structure.
Patent Information
- Application Number
- CN202411582711.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-25
AI Technical Summary
Traditional concrete is susceptible to corrosion, freeze-thaw damage in harsh environments, resulting in structural failure and shortening of service life. It is difficult for existing admixtures to effectively deal with multiple environmental damage.
Using a modified concrete material including cement, sand, gravel, basalt fiber, epoxy resin, curing agent and defoaming agent, the porosity and water absorption of concrete are reduced through the filling and protection of epoxy resin to form a dense The protective layer prevents the penetration of corrosive media.
It significantly improves the corrosion resistance and freeze-thaw resistance of concrete, extends the service life of the structure, and shows excellent durability and stability especially in marine environments, saline-alkali lands and areas undergoing freeze-thaw cycles.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the field of concrete materials, and in particular relates to a salt corrosion resistant modified concrete material and a preparation method thereof. Background Art
[0002] With the development of modern building materials, concrete has been widely used in infrastructure projects such as buildings and bridges. However, concrete is susceptible to corrosion, freeze-thaw damage and other problems in harsh environments (such as saline soil, high humidity environment, freeze-thaw cycles, etc.), resulting in structural failure and shortened service life. In these environments, the durability and corrosion resistance of concrete have become key technical issues that need to be solved urgently.
[0003] Traditional concrete formulas show low resistance to salt corrosion and freeze-thaw when facing these extreme environments, especially in environments containing corrosive media such as sulfate ions, magnesium ions, and chloride ions, where the concrete structure will deteriorate rapidly. Although some common admixtures can improve the performance of concrete to a certain extent, their effects are still limited and it is difficult to effectively cope with multiple environmental damages.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art, provide a salt-corrosion resistant modified concrete material and a preparation method thereof, and solve the problems raised in the above-mentioned background technology.
[0006] In order to solve the above technical problems, the basic concept of the technical solution adopted by the present invention is: A salt corrosion resistant modified concrete material comprises the following components: 16-18 parts of cement, 40.42-41.17 parts of sand, 67.08 parts of gravel, 0.3-0.75 parts of basalt fiber, 1-5 parts of epoxy resin, 0.2-1 parts of curing agent, 0.2-1 parts of defoaming agent and 11.99 parts of water.
[0007] Optionally, the particle size of the sand is 0.5-2 mm, the particle size of the stone is 5-25 mm, the length of the basalt fiber is 6-12 mm, and the diameter is 10-20 μm.
[0008] Optionally, the cement is ordinary Portland cement or high sulfate-resistant cement.
[0009] Optionally, the epoxy resin is DY-128-50 water-based epoxy resin, the curing agent is DY-175 curing agent, and the defoaming agent is LJ-618 defoaming agent.
[0010] Optionally, the concrete material has a water absorption of 20-24.5% and a dry density of 2000-2300 kg / m³.
[0011] A method for preparing the above-mentioned salt corrosion resistant modified concrete material comprises the following steps: Step (1): Add cement, sand, gravel and basalt fiber into a mixing device in proportion, and dry mix for 1-2 minutes to form a preliminary mixture after the solid components are evenly distributed.
[0012] Step (2): After the dry mixing is completed, gradually add a predetermined amount of water to the mixing equipment while maintaining stirring, and continue wet mixing for 4-5 minutes to allow the water and solid components to fully combine to form a mixture.
[0013] Step (3): While wet mixing, separately mix the epoxy resin, curing agent and defoaming agent in proportion and stir for 2-3 minutes until a modified emulsion is formed.
[0014] The epoxy resin component contained in the emulsion of the present invention plays a key filling and protective role inside the concrete. The molecular structure of the epoxy resin has good fluidity and can penetrate into tiny pores and voids during the mixing process of the concrete, effectively filling the micropores in the concrete structure and reducing the porosity of the concrete. Porosity is an important factor affecting the water absorption rate of concrete. By filling these pores, the epoxy resin can significantly reduce the water absorption rate of the concrete and reduce the infiltration of moisture and other corrosive media. This characteristic is particularly suitable for use in a salt corrosion environment, avoiding the problem that traditional concrete is prone to corrosion when exposed to moisture and salt for a long time.
[0015] When epoxy resin and curing agent react chemically, the cross-linked structure formed between them further enhances the strength and stability of the material. The result of the curing reaction is the formation of a strong and dense protective layer on the surface and inside of the concrete. This protective layer not only has good water resistance, but also effectively prevents the penetration of corrosive media. These corrosive ions usually accelerate the corrosion of steel bars in reinforced concrete, causing concrete cracking and spalling, but through the presence of the epoxy resin protective layer, the penetration of these corrosive media is greatly slowed down, thereby significantly improving the corrosion resistance of concrete.
[0016] In addition, an appropriate amount of defoamer is added in the present invention. During the mixing and curing process of concrete, the defoamer can effectively reduce the bubbles generated during the mixing process. If these bubbles are not eliminated, they will become weak points inside the concrete, resulting in insufficient local strength and providing a path for water and corrosive media to penetrate. The defoamer makes the internal structure of the concrete more compact and uniform, further improves its density, reduces potential penetration channels, and thus enhances the anti-penetration performance of the concrete.
[0017] By using epoxy resin and curing agent in combination, and adding defoamer, the present invention significantly improves the comprehensive performance of concrete, making it show excellent durability and stability in high humidity, high salinity or other corrosive environments. In particular, in marine environments, saline-alkali lands and areas that often experience freeze-thaw cycles, concrete is often exposed to salts, moisture and temperature changes. The modified concrete of the present invention can effectively resist these harsh conditions and extend the service life of buildings and structures.
[0018] In addition, the existence of this protective layer is not limited to the surface effect, it can penetrate into the internal structure of the concrete, so that the entire material has better long-term protection ability. This deep protection greatly reduces the frequency and cost of later maintenance, making the modified concrete material of the present invention have significant economic and social benefits, and is particularly suitable for infrastructure projects such as bridges, roads, and marine facilities that need to be exposed to harsh environments for a long time.
[0019] Step (4): Add the modified emulsion to the concrete mixture that has been evenly mixed, and continue stirring for 3 minutes. After the modified emulsion is evenly distributed in the concrete mixture, the final modified concrete material is obtained.
[0020] The salt-corrosion-resistant modified concrete material and preparation method thereof according to claim 1 is characterized in that the stirring speed during the dry mixing process in step (1) is 30-60 rpm, and the stirring speed during the wet mixing process in step (2) is 60-80 rpm.
[0021] Optionally, the stirring speed when preparing the modified emulsion in step (3) is 60-80 rpm.
[0022] Optionally, in step (4), the stirring speed when mixing the modified emulsion and the mixture is 80-120 rpm.
[0023] After adopting the above technical solution, the present invention has the following beneficial effects compared with the prior art. Of course, any product implementing the present invention does not necessarily need to achieve all the advantages described below at the same time: 1. The epoxy resin component contained in the emulsion of the present invention fills tiny pores in the concrete, significantly reduces the porosity and water absorption, forms a dense protective layer after solidification, effectively prevents the penetration of corrosive media such as sulfate and chloride ions, and enhances the corrosion resistance of the concrete; at the same time, the addition of the defoamer further reduces the bubbles in the mixing process, making the concrete structure more uniform and compact, reducing the penetration path, and significantly improving the durability and stability of the concrete in harsh environments such as high humidity, high salinity and freeze-thaw cycles.
[0024] 2. By combining basalt fiber with epoxy resin emulsion, the performance of the concrete material of the present invention remains relatively stable during multiple freeze-thaw cycles. Basalt fiber enhances the crack resistance of the material and avoids the expansion of cracks caused by volume change of concrete during freeze-thaw; epoxy resin emulsion improves the density of the material, reduces the freezing and expansion of water inside the concrete, and fundamentally improves the freeze-thaw resistance of the concrete. DETAILED DESCRIPTION
[0025] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0026] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0027] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0028] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present application description and examples are exemplary only.
[0029] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0030] The embodiment of the present invention discloses a salt corrosion resistant modified concrete material, comprising the following components: 16-18 parts of cement, 40.42-41.17 parts of sand, 67.08 parts of gravel, 0.3-0.75 parts of basalt fiber, 1-5 parts of epoxy resin, 0.2-1 parts of curing agent, 0.2-1 parts of defoaming agent, and 11.99 parts of water.
[0031] In some embodiments of the present invention, it is characterized in that the concrete material has a water absorption rate of 20-24.5% and a dry density of 2000-2300 kg / m³.
[0032] A method for preparing the above-mentioned salt corrosion resistant modified concrete material comprises the following steps: Step (1): Add cement, sand, gravel and basalt fiber into a mixing device in proportion, and dry mix for 1-2 minutes to form a preliminary mixture after the solid components are evenly distributed.
[0033] Step (2): After the dry mixing is completed, gradually add a predetermined amount of water to the mixing equipment while maintaining stirring, and continue wet mixing for 4-5 minutes to allow the water and solid components to fully combine to form a mixture.
[0034] Step (3): While wet mixing, separately mix the epoxy resin, curing agent and defoaming agent in proportion and stir for 2-3 minutes until a modified emulsion is formed.
[0035] Step (4): Add the modified emulsion to the concrete mixture that has been evenly mixed, and continue stirring for 3 minutes. After the modified emulsion is evenly distributed in the concrete mixture, the final modified concrete material is obtained.
[0036] In some embodiments of the present invention, the stirring speed during the dry mixing process in step (1) is 30-60 rpm, and the stirring speed during the wet mixing process in step (2) is 60-80 rpm.
[0037] In some embodiments of the present invention, the stirring speed when preparing the modified emulsion in step (3) is 60-80 rpm.
[0038] In step (4), the stirring speed when mixing the modified emulsion and the mixture is 80-120 rpm.
[0039] The present invention will now be further described in detail with reference to embodiments.
[0040] It should be noted that all raw materials in the examples of the present invention were obtained through commercial sources.
[0041] The epoxy resin used in the following examples is DY-128-50 water-based epoxy resin, the curing agent is DY-175 curing agent, the defoaming agent is LJ-618 defoaming agent, the cement is ordinary Portland cement, the particle size of the sand is 1 mm, the particle size of the gravel is 3 mm, and the length of the basalt fiber is 4 mm and the diameter is 12 μm.
[0042] Embodiment 1: A salt corrosion resistant modified concrete material and a preparation method thereof, comprising the following steps: Step (1): 19 parts of cement, 41.02 parts of sand, 67.08 parts of gravel, and 0.15 parts of basalt fiber are added to a mixing device in proportion, the mixing speed is controlled at 40 rpm, and dry mixing is performed for 2 minutes to ensure that the solid components are evenly distributed to form a preliminary dry mixture.
[0043] Step (2): After the dry mix is completed, gradually add 11.99 parts of water while maintaining the stirring speed at 60 rpm, and perform wet mixing for 5 minutes to allow the water to fully combine with the dry mix to form a uniform wet mix.
[0044] Step (3): In another stirring container, mix 1 part of DY-128-50 waterborne epoxy resin, 0.2 parts of DY-175 curing agent, and 0.2 parts of LJ-618 defoaming agent in proportion, control the stirring speed at 80 rpm, and stir for 2 minutes until a uniform modified emulsion is formed.
[0045] Step (4): Add the modified emulsion to the wet mixture, control the stirring speed at 80 rpm, and continue stirring for 3 minutes to ensure that the modified emulsion is evenly distributed in the concrete mixture, and finally obtain a modified concrete material.
[0046] Embodiment 2: A salt corrosion resistant modified concrete material and a preparation method thereof, comprising the following steps: Step (1): 18 parts of cement, 40.87 parts of sand, 67.08 parts of gravel, and 0.3 parts of basalt fiber are added to a mixing device in proportion, the mixing speed is controlled at 40 rpm, and dry mixing is performed for 2 minutes to ensure that the solid components are evenly distributed to form a preliminary dry mixture.
[0047] Step (2): After the dry mix is completed, gradually add 11.99 parts of water, control the stirring speed at 60 rpm, and perform wet mixing for 5 minutes to fully mix the water and the dry mix to form a uniform wet mix.
[0048] Step (3): In another container, mix 2 parts of DY-128-50 waterborne epoxy resin, 0.4 parts of DY-175 curing agent, and 0.4 parts of LJ-618 defoaming agent, stirring at a speed of 80 rpm for 2 minutes until a uniform modified emulsion is formed.
[0049] Step (4): Mix the modified emulsion with the wet mixture, control the stirring speed at 80 rpm, and continue stirring for 3 minutes to ensure that the modified emulsion is evenly distributed in the concrete, thereby obtaining a modified concrete material.
[0050] Embodiment 3: A salt corrosion resistant modified concrete material and a preparation method thereof, comprising the following steps: Step (1): 17 parts of cement, 40.72 parts of sand, 67.08 parts of gravel, and 0.45 parts of basalt fiber are added to a mixing device in proportion, the mixing speed is controlled at 40 rpm, and dry mixing is performed for 2 minutes to evenly distribute the solid components to form a preliminary dry mixture.
[0051] Step (2): After the dry mix is completed, gradually add 11.99 parts of water, control the stirring speed at 60 rpm, and wet mix for 5 minutes to ensure that the water and dry mix are fully combined to form a wet mix.
[0052] Step (3): Mix 3 parts of DY-128-50 waterborne epoxy resin, 0.6 parts of DY-175 curing agent, and 0.6 parts of LJ-618 defoaming agent, stirring at a speed of 70 rpm for 2.5 minutes until a uniform modified emulsion is formed.
[0053] Step (4): Add the modified emulsion to the wet mixture, control the stirring speed at 80 rpm, and continue stirring for 3 minutes to ensure that the modified emulsion is evenly distributed in the concrete mixture to obtain a modified concrete material.
[0054] Embodiment 4: A salt corrosion resistant modified concrete material and a preparation method thereof, comprising the following steps: Step (1): 16 parts of cement, 40.57 parts of sand, 67.08 parts of gravel, and 0.6 parts of basalt fiber are added to a mixing device in proportion, the mixing speed is controlled at 40 rpm, and dry mixing is performed for 2 minutes to ensure that the solid components are evenly distributed to form a preliminary dry mixture.
[0055] Step (2): After the dry mix is completed, 11.99 parts of water is gradually added, the stirring speed is controlled at 60 rpm, and wet mix is performed for 5 minutes to allow the water to fully combine with the dry mix to form a wet mix.
[0056] Step (3): 4 parts of DY-128-50 waterborne epoxy resin, 0.8 parts of DY-175 curing agent, and 0.8 parts of LJ-618 defoaming agent were mixed at a stirring speed of 60 rpm for 3 minutes to obtain a uniform modified emulsion.
[0057] Step (4): Mix the modified emulsion with the wet mixture, control the stirring speed at 80 rpm, and continue stirring for 3 minutes to ensure that the modified emulsion is evenly distributed in the concrete mixture, and finally obtain a modified concrete material.
[0058] Embodiment 5: A salt corrosion resistant modified concrete material and a preparation method thereof, comprising the following steps: Step (1): 15 parts of cement, 40.42 parts of sand, 67.08 parts of gravel, and 0.75 parts of basalt fiber are added to a mixing device in proportion, the mixing speed is controlled at 60 rpm, and dry mixing is performed for 2 minutes to ensure that the components are evenly distributed to form a preliminary dry mixture.
[0059] Step (2): After the dry mix is completed, gradually add 11.99 parts of water, control the stirring speed at 60 rpm, and perform wet mixing for 5 minutes to ensure that the water and the dry mix are fully combined to form a uniform wet mix.
[0060] Step (3): Mix 5 parts of DY-128-50 waterborne epoxy resin, 1 part of DY-175 curing agent, and 1 part of LJ-618 defoaming agent, stirring at a speed of 60 rpm for 3 minutes to obtain a uniform modified emulsion.
[0061] Step (4): Add the modified emulsion to the wet mixture, control the stirring speed at 80 rpm, and continue stirring for 3 minutes to ensure that the modified emulsion is evenly distributed in the concrete, and finally obtain a modified concrete material.
[0062] Comparative Example 1: A salt corrosion resistant modified concrete material and a preparation method thereof, comprising the following steps: Add 20 parts of cement, 41.17 parts of sand and 67.08 parts of gravel into the mixing equipment in proportion, control the mixing speed at 50 rpm, and dry mix for 2 minutes to ensure that the ingredients are evenly distributed to form a preliminary dry mixture.
[0063] After the dry mixing is completed, 11.99 parts of water are gradually added, the stirring speed is controlled at 60 rpm, and stirring is continued for 5 minutes to finally obtain ordinary concrete material.
[0064] Performance Testing 1. Measurement method The modified concrete and ordinary concrete obtained in Examples 1-5 and Comparative Example 1 were respectively prepared into specimens of standard sizes. The specific sizes were 100mm×100mm×100mm cubic specimens and 100mm×100mm×400mm prism specimens. Several specimens were prepared for each type of concrete to ensure the repeatability of the test and the accuracy of the data. The prepared specimens were placed in a standard curing room with a relative humidity of not less than 95% and a temperature of 20±2°C for 28 days of standard curing. After the standard curing period, the strength and stability of the specimens met the design requirements and can be used for subsequent performance tests.
[0065] During the performance test, a cubic specimen with a size of 100mm×100mm×100mm was first selected to determine the dry density and water absorption rate. The dry density test can reflect the compactness of concrete, while the water absorption rate is used to evaluate the ability of concrete materials to resist water penetration. Lower water absorption means that the porosity of concrete is smaller, and the material has stronger corrosion resistance and durability.
[0066] In order to simulate the salt corrosion environment in southern Xinjiang, the titration method was used to determine the content of SO4²⁻, Mg²⁺, Cl⁻, CO3²⁻ and HCO3⁻ ions at 0-5cm on the surface of a saline soil in southern Xinjiang, and the concentration distribution of these ions in the soil was determined. These ions are commonly found in saline soil and can cause corrosion damage to concrete materials. Based on the measured ion content, a composite salt solution (F1) with a base concentration of 1.99% was prepared, which was used to simulate the corrosion conditions in the saline soil environment.
[0067] In the corrosion test, the specimens of Examples 1-5 and Comparative Example 1 with a size of 100 mm × 100 mm × 100 mm were immersed in the prepared F1 solution. The corrosion tests were carried out at corrosion ages of 30 days, 60 days and 90 days to simulate the long-term service conditions of concrete in a corrosive environment. At each corrosion age, the compressive strength corrosion resistance coefficient of the specimens was measured to evaluate the durability of the concrete in a corrosive environment.
[0068] Table 1 Ion content of saline soil in Daoxiang Road, Wensu County
[0069] Table 2 Concentration of compound salt solution
[0070] A 100mm×100mm×400mm concrete specimen was placed in a freeze-thaw cycle specimen box. Before the test began, a 1.99% Na2SO4 solution (sodium sulfate solution) was injected into the specimen box. To ensure that the specimen was in full contact with the corrosive medium, the liquid level of the solution was designed to be 10mm above the top of the specimen to ensure that the specimen was completely immersed in the corrosive solution.
[0071] The test process includes repeated freeze-thaw cycles. Each freeze-thaw cycle involves freezing the concrete specimens immersed in Na2SO4 solution at -18°C for several hours to freeze the internal water, and then moving them to a room temperature environment (about 20°C) for thawing and keeping them for several hours. Through this cycle, the actual working conditions under low temperatures in winter are simulated. In order to evaluate the damage of the material, the performance of the specimens was tested after 50 and 100 freeze-thaw cycles.
[0072] After each cycle, the main test indicators include: Mass loss rate: The mass loss rate is calculated by measuring the mass change of the specimen before and after the freeze-thaw cycle. This indicator is used to evaluate the degree of loss of concrete structures in freeze-thaw and salt corrosion environments. A lower mass loss rate means that the structure of the concrete material is more stable and has stronger damage resistance.
[0073] Dynamic elastic modulus loss rate: Dynamic elastic modulus is an important indicator to measure the elastic properties of materials. During the freeze-thaw cycle, the repeated freezing and thawing of water inside the concrete can easily cause the expansion and damage of internal microcracks, resulting in a decrease in the elastic modulus of the material. By measuring the change in dynamic elastic modulus before and after the freeze-thaw cycle and calculating the loss rate, the durability and crack resistance of the material can be judged.
[0074] 2. The test results are shown in Tables 3 to 5 below: Table 3 Dry density and water absorption test results of Examples 1-5 Comparative Example 1
[0075] Table 4 Compressive strength and corrosion resistance coefficient test results of Example 1-5 Comparative Example 1
[0076] Table 5 Test results of mass loss rate and dynamic elastic modulus loss rate of Example 1-5 Comparative Example 1
[0077] As shown in Table 3, the dry density of Examples 1-5 is higher than that of Control Example 1. The dry density of Example 2 is the highest, which is 2324 kg / m³, while the dry density of Control Example 1 is only 2280 kg / m³. This shows that in Examples 1-5, by adding basalt fiber and modified emulsion (epoxy resin, curing agent and defoaming agent), the density of concrete is significantly improved, the porosity is reduced, and the strength and durability of the material are enhanced.
[0078] The water absorption rates of Examples 1-5 are all lower than that of Control Example 1. The water absorption rate of Example 2 is the lowest, which is 24.1%, while the water absorption rate of Control Example 1 is 25.0%. Lower water absorption rate means that the porosity in the concrete is smaller and the material is denser, thereby improving the material's resistance to water penetration and reducing the possibility of water and corrosive ions entering the material.
[0079] It can be seen from Table 4 that in the 30-day corrosion test, the compressive strength corrosion resistance coefficients of Examples 1-5 are all higher than those of Control Example 1. The corrosion resistance coefficient of Example 2 is the highest, reaching 0.994, while that of Control Example 1 is only 0.971. This shows that in the early stage of corrosion, the corrosion resistance of Example 2 is significantly better than that of the Control Example. As the corrosion time increases, the compressive strength corrosion resistance coefficients of Examples 1-5 are all better than those of Control Example 1, especially at 90 days, when Example 2 remains at 0.923, while that of Control Example 1 is only 0.884. This shows that under long-term corrosion conditions, Example 2 has a higher strength retention rate and stronger durability.
[0080] As can be seen from Table 5, the mass loss rates of Examples 1-5 are significantly lower than those of Control Example 1. In particular, the mass loss rate of Example 2 is the lowest, which is 0.227% and 0.935% after 50 and 100 salt corrosion-freeze-thaw cycles, respectively, while that of Control Example 1 is 0.681% and 2.560%, respectively. The lower mass loss rate indicates that Example 2 is more resistant to damage in salt corrosion and freeze-thaw cycles, and the structure of the material is more stable. The dynamic elastic modulus loss rates of Examples 1-5 are also lower than those of Control Example 1. The dynamic elastic modulus loss rates of Example 2 are 3.403% (50 cycles) and 7.453% (100 cycles), respectively, while those of Control Example 1 are 5.983% and 11.613%, respectively. This shows that after experiencing salt corrosion and freeze-thaw cycles, the elastic modulus of the material in Example 2 is better maintained, and the structural performance degrades more slowly.
[0081] DY-128-50 waterborne epoxy resin, DY-175 curing agent and LJ-618 defoamer were added in Examples 1-5. These modified components effectively filled the pores of concrete and enhanced the density and corrosion resistance of the material. Epoxy resin has good adhesion and chemical corrosion resistance, curing agent can accelerate the hardening process of the material, and defoamer reduces bubbles in concrete and improves the overall density. Moreover, basalt fiber is a high-strength, corrosion-resistant reinforcing material that can significantly improve the crack resistance, tensile strength and impact resistance of concrete. With the increase of fiber content, the crack resistance and durability of the material are further improved, which is particularly evident in freeze-thaw cycles and corrosive environments. Moreover, the dry mixing and wet mixing time in the embodiment have been precisely controlled to ensure that the components are evenly distributed, especially the modified emulsion is fully mixed with concrete, which further improves the uniformity and stability of the material.
[0082] The present invention is not limited to the above-mentioned embodiments. Anyone should be aware that any structural changes made under the enlightenment of the present invention, and any technical solutions that are the same or similar to the present invention, fall within the protection scope of the present invention. The technology, shape, and structural parts not described in detail in the present invention are all well-known technologies.
Claims
1. A salt corrosion resistant modified concrete material, characterized in that: The concrete material comprises the following components: 16-18 parts of cement, 40.42-41.17 parts of sand, 67.08 parts of gravel, 0.3-0.75 parts of basalt fiber, 1-5 parts of epoxy resin, 0.2-1 parts of curing agent, 0.2-1 parts of defoaming agent and 11.99 parts of water.
2. The salt corrosion resistant modified concrete material according to claim 1, characterized in that: The particle size of the sand is 0.5-2 mm, the particle size of the stone is 5-25 mm, the length of the basalt fiber is 6-12 mm, and the diameter is 10-20 μm.
3. The salt corrosion resistant modified concrete material according to claim 1, characterized in that: The cement is ordinary Portland cement or high sulfate resistance cement.
4. The salt corrosion resistant modified concrete material according to claim 1, characterized in that: The epoxy resin is DY-128-50 type water-based epoxy resin, the curing agent is DY-175 type curing agent, and the defoaming agent is LJ-618 type defoaming agent.
5. The salt corrosion resistant modified concrete material according to claim 1, characterized in that: The water absorption rate of concrete material is 20-24.5% and the dry density is 2000-2300 kg / m³.
6. A method for preparing the salt corrosion resistant modified concrete material according to any one of claims 1 to 5, characterized in that: The following steps are involved: Step (1): Add cement, sand, gravel and basalt fiber into a mixing device in proportion, and dry mix for 1-2 minutes to form a preliminary mixture after the solid components are evenly distributed; Step (2): After the dry mixing is completed, gradually add a predetermined amount of water to the mixing device while maintaining stirring, and continue wet mixing for 4-5 minutes to allow the water and solid components to fully combine to form a mixture; Step (3): While wet mixing, separately mix the epoxy resin, curing agent and defoaming agent in proportion and stir for 2-3 minutes until a modified emulsion is formed; Step (4): Add the modified emulsion to the concrete mixture that has been evenly mixed, and continue stirring for 3 minutes. After the modified emulsion is evenly distributed in the concrete mixture, the final modified concrete material is obtained.
7. The method for preparing a salt corrosion resistant modified concrete material according to claim 6, characterized in that: The stirring speed during the dry mixing process in step (1) is 30-60 rpm, and the stirring speed during the wet mixing process in step (2) is 60-80 rpm.
8. The method for preparing a salt corrosion resistant modified concrete material according to claim 6, characterized in that: When preparing the modified emulsion in step (3), the stirring speed is 60-80 rpm.
9. The method for preparing a salt corrosion resistant modified concrete material according to claim 6, characterized in that: In step (4), the stirring speed when mixing the modified emulsion and the mixture is 80-120 rpm.